Optimisation analysis of gear transmission system of the automobile gearbox based on the MASTA software. (2015) - Zhao, Youjia; Wang, Feng; Li, Yongxiang; Dong, Lujian; Yu, Fujin
The dynamic meshing characteristics of gear drives have been a major concern in the design of gear transmission system. The paper takes a five-speed gearbox as an example to accomplish the gear mesh analysis based on the MASTA software. According to the transmission characteristics of gear transmission system of the automobile gearbox, the simulation modelling of the gearbox is built to determine a reasonable configuration of the overall gearbox, and then simulate the actual load conditions and complete the process analysis for the gear. The computational results show that using the specialized software MASTA for transmission modelling and simulation analysis can heavily improve the design level and mechanical properties of the gearbox. It is a useful work for the industry to employ the powerful MASTA to design gearbox from the whole system approach. In conclusion the present work can provide effective guidance for the fault diagnosis of gear meshing.